A Framework for the Risk Assessment and Management of Gene Drive Technology in Contained Use. (March 2018) - van der Vlugt, Cécile J. B.; Brown, David D.; Lehmann, Kathleen; Leunda, Amaya; Willemarck, Nicolas
The utilisation of the CRISPR/Cas9 technology has sparked a renewed interest in gene drive mechanisms. These mechanisms of biased inheritance may yield promising applications in the fields of vector control and nature conservation. However, the same properties that will enable these applications may also pose a risk if organisms that are equipped with gene drive cassettes are unintentionally released into the environment. Although several groups of scientists and regulators have started to address these safety concerns, there are currently no dedicated guidelines published on the required risk assessment and minimal control measures applicable to gene drive organisms in contained use. To fill this gap, this paper describes a fundamental approach to assessing the risks of these organisms while handled in a contained laboratory environment. Based on the likelihood that an adverse effect will arise from the handling of a gene drive organism and the severity of this effect, three risk classes for contained use activities are presented. Finally, specific minimum requirements regarding physical measures and working practices are proposed according to the presented risk classes and tailored to activities with rodents, insects, and fungi, which are most likely to be used for gene drive applications in the near future.